Bayesian Hierarchy Non-stationary Neural Network on Short Term Prediction Wind Power Model for Measuring Work Capacity of Wind Turbine - Prasetyowati, A.; Sudiana, D.; Sudibyo, H. (International Journal of Engineering and Technology, 2019)
Wind energy is environmentally friendly energy, intermittent problems often occur in the generation of this energy in tropical wind lands. Due to this problem the working capacity of wind turbines does not have an average work size. So that it is difficult for operators to calculate the capacity produced by the wind turbines which are located on the observation land. In this study wind speed identification using Peaks Over Threshold (POT) method with extreme data distribution pattern of wind speed generated by pareto distribution (GPD). Estimation of GPD parameters is carried out using the Bayesian Hierarchy Model (BHM) to overcome the problem of data limitations and uncertainty of parameters in determining the capacity of the wind turbine. Regression model to get a prediction of wind turbine working capacity using Neural Network (NN). The Bayes Neural Network model provides the smallest error in wind power prediction compared to the Neural Network (NN) prediction model and the Wavelet Decomposition Neural Network (WDNN) model.Â Â